The Exploitation of Indonesian Migrant Workers When Abroad - Prabaningrum Kusumawati, Mustika; Khairun Hamrany, Ahmad (KnE Social Sciences, 2023)
The exploitation of Indonesian migrant workers continues to be an issue. They struggle to avoid falling prey to exploitation and trafficking. This study used normative legal research, which included many complaints noted in the BP2MI data. However, migrant workers who are prevented from complaining to the government due to their circumstances were not included in the calculation. The state must be present in order to safeguard migrant workers, and this protection must be not only written legislation but also tangible actions that serve as evidence of the presence of the state. Keywords: Problems, Exploitation, Indonesian Migrant Workers, Abroad